Structural Variations of Bacterial Community Driven by Sphagnum Microhabitat Differentiation in a Subalpine Peatland - Tian, Wen; Wang, Hongmei; Xiang, Xing; Wang, Ruicheng; Xu, Ying (Frontiers in Microbiology, 2019)
Sphagnum microbiomes play an important role in the northern peatland ecosystems. However, information about above and belowground microbiomes related to Sphagnum at subtropical area remains largely limited. In this study, microbial communities from Sphagnum palustre peat, S. palustre green part and S. palustre brown part at the Dajiuhu Peatland, central China were investigated via 16S rRNA gene amplicon sequencing. Results indicated that Alphaproteobacteria was the dominant class in all samples, and the class Acidobacteria and Gammaproteobacteria were abundant in S. palustre peat and S. palustre brown part samples, respectively. In contrast, the class Cyanobacteria dominated in S. palustre green part samples. Microhabitat differentiation mainly contributes to structural differences of bacterial microbiome. In the S. palustre peat, microbial communities were significantly shaped by water table and total nitrogen content. Our study is a systematical investigation on above and belowground bacterial microbiome in a subalpine Sphagnum peatland and the results offer new knowledge about the distribution of bacterial microbiome associated with different microhabitats in subtropical area.